How perceived interparental conflict shapes academic engagement in Chinese adolescents: a moderated mediation model - Li, Yu; Han, YuMei (Frontiers in Education, 2025)
ObjectivesThis study aimed to investigate the impact of Chinese high school students’ perceived interparental conflict on their academic engagement, with a focus on the mediating roles of positive and negative academic emotions and the moderating role of emotional intelligence.BackgroundIn China, parents often suppress interparental conflicts until after their children’s college entrance exams to avoid disrupting the latter’s academic performance. However, unresolved interparental conflict may impair adolescents’ psychological wellbeing and academic engagement. Grounded in the Cognitive-Contextual Theory and the Emotional Security Theory, this research explored how perceived interparental conflict influences academic engagement through academic emotions, and how emotional intelligence buffers these adverse effects.MethodsThe study used data from 257 high school students in City G, Province S of China. Hierarchical regression analysis was employed to test the proposed mediating and moderating hypotheses.ResultsPerceived interparental conflict had a significant negative impact on academic engagement; both positive and negative academic emotions partially mediated the relationship between perceived interparental conflict and academic engagement; emotional intelligence weakened the negative impact of perceived interparental conflict on positive academic emotions, and mitigated the positive impact of the former on negative academic emotions.ConclusionThis study confirmed the negative impact of perceived interparental conflict on high school students’ academic engagement, revealed the mechanism by which interparental conflict in the family environment influences academic engagement, and proposed targeted measures and practical suggestions to prioritize students’ academic emotional regulation and enhance their emotional intelligence in both school and family contexts.